The Effect of Promotions and Word-of-Mouth on Service Usage Decisions, Moderated By Service Quality on Instagram Among Aya Makeup Consumers - Diansyah Diansyah; Amin Alfachri Ramadhan Hurasan (Eduvest - Journal of Universal Studies, 2026)
This research aims to analyze the influence of promotion and word of mouth on the decision to use Aya Makeup services through Instagram with service quality as a moderation variable. The study used a quantitative approach with a survey method of 105 respondents who had used Aya Makeup's services. The sampling technique used purposive sampling, while the data analysis was carried out using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of the SmartPLS 3.0 application. The results of the study show that promotion has a positive and significant effect on the decision to use services. In addition, word of mouth and service quality have also been proven to have a positive and significant effect on service usage decisions. Service quality has the greatest influence on improving service usage decisions compared to other variables. However, the quality of service is not able to moderate the relationship between promotion and the decision to use the service nor the relationship between word of mouth and the decision to use the service. A determination coefficient value (R²) of 0.840 indicates that promotion, word of mouth, and service quality are able to explain 84% of the variation in service usage decisions. These findings indicate that increasing the effectiveness of promotions, strengthening consumer recommendations, and providing quality services are important factors in encouraging consumer decisions to use Aya Makeup services.